Glycosphingolipid-associated β-1, 4 galactosyltransferase is elevated in patients with systemic lupus erythematosus. Issue 1 (13th July 2020) - Sadras, Vignesh; Petri, Michelle A; Jones, Steven Richard; Peterlin, Barbara Lee; Chatterjee, Subroto
Abstract : Objective: β-1, 4 galactosyltransferase-V (β-1, 4 GalT-V) is an enzyme that synthesises a glycosphingolipid known as lactosylceramide, which has been implicated in general inflammation and atherosclerosis. We asked if β-1, 4 GalT-V was present at elevated levels in patients with SLE, a disease which is associated with increased risk of atherosclerosis. Methods: In this case–control observational study, serum samples were obtained from patients with SLE who are part of the Johns Hopkins Lupus Cohort. Control serum samples were obtained from healthy adult community members recruited from the Baltimore area. All serum samples (n=50 in the SLE group and n=50 in the healthy control group) were analysed with enzyme-linked immunoassays. These assays used antibodies raised against antigens that enabled us to measure the absorbance of oxidised phosphocholines per apolipoprotein B-100 (ox-PC/apoB) and the concentration of lipoprotein(a) (Lp(a)) and β-1, 4 GalT-V. Results: Absorbance of ox-PC/apoB and concentrations of Lp(a) and β-1, 4 GalT-V were significantly higher in the SLE serum samples as compared with the control serum (p<0.0001). Conclusions: We conclude that patients with SLE have elevated levels of β-1, 4 GalT-V and ox-PC, which have previously been recognised as risk factors for atherosclerosis.